Acoustics for engineers : troy lectures - Blauert, Jens 1938-; Xiang, Ning 1955- (Berlín Springer, 2008)
This book provides the material for an introductory course in engineering acoustics for students with basic knowledge in mathematics. It is based on extensive teaching experience at the university level.
Keywords: INGENIERÍA ACÚSTICA